The anomaly of the fertility decline in India's Kerala State : a field investigation - Zachariah, K. C. (Washington, D.C., U.S.A. : World Bank, 1984)
The study concludes that the fertility decline in Kerala was caused by an optimum sequence of the commonly recognized determinants of fertility trends.
Summaries in French and Spanish.
Spine title: The fertility decline in India's Kerala State.
"October 1984"--T.p. verso.
Bibliography: p. 193-197.
rpm 19/02/2019
Ref
Keywords: Fertility, Human; Kerala (India)